ANALISIS KESULITAN BELAJAR PESERTA DIDIK SEKOLAH DASAR TERHADAP KEMAMPUAN KONEKSI MATEMATIS DALAM STATISTIKA - Sri Haryanti; Fitri Lastini; Nining Setyaningsih; Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe how fifth-grade students at SD Negeri 03 Jatiwarno, Jatipuro, Karanganyar solve statistics problems based on their mathematical connection abilities and to identify the learning difficulties they face. The research method used is descriptive qualitative, with ten student participants. Data were collected through essay tests and interviews to obtain an in-depth understanding of the mistakes and the factors causing learning difficulties. The results showed that students have varying levels of mathematical connection abilities, with most in the moderate category. The learning difficulties faced by students include errors in reading questions, understanding questions, transforming formulas, process skills, and writing conclusions. Factors influencing learning difficulties include teaching methods, classroom atmosphere, parental involvement, social environment, interest in mathematics, and laziness to study. This study also proposes several teaching strategies that can help students better understand and master statistical material, including contextual and relevant approaches, interactive learning, the use of visual media, and proper curriculum planning and organization. The implementation of these strategies is expected to enhance students' understanding of statistical material and their mathematical connection abilities, thereby minimizing learning difficulties and optimizing learning outcomes.